Single-tablet combination therapy of Macitentan/Tadalafil for patients with pulmonary arterial hypertension: qualitative interview study of the A DUE phase 3 trial - Fan, Fenling; Davis, Stacy; Burbridge, Claire; Chin, Kelly; Friberg, Michael; Grünig, Ekkehard; Hughes, Melanie; Jansa, Pavel; Linder, Jörg; Rafalski, Jennifer; Rodriguez, Alvaro Agustin; Randall, Jason A. (Advances in therapy, 2025)
INTRODUCTION: This study explored patient and clinician perspectives on a new fixed-dose combination of macitentan and tadalafil (M/T FDC) in a once-daily single tablet for treatment of pulmonary arterial hypertension (PAH). - METHODS: Qualitative semi-structured interviews were conducted during the open-label period of the global, phase 3 A DUE clinical trial that evaluated M/T FDC. A subset of enrolled patients (N = 26) and site investigators (N = 18 clinicians) were interviewed. Patients received four tablets during double-blind treatment and could be in one of three arms (macitentan + placebo; tadalafil + placebo; M/T FDC + placebo) followed by M/T FDC (one tablet) during the open-label period. Patients and clinicians were asked to share their experience of pre-trial PAH medication, double-blind treatment, and open-label M/T FDC. Thematic analysis was conducted on blinded data. - RESULTS: Patients preferred the M/T FDC tablet (open-label) over the four tablets during double-blind treatment. Patients were satisfied with M/T FDC, highlighting its positive impact on their psychological well-being, through reducing stress associated with managing multiple pills. All patients indicated that having a single, once-a-day pill for PAH was more convenient and associated with greater treatment adherence. Clinicians highlighted that their patients have a high daily pill burden for PAH and other comorbidities, and prefer treatments with an oral mode of administration that reduce the number of daily pills required. Clinicians felt that M/T FDC would be well received in clinical practice and potentially assist in implementing guideline-recommended combination treatment of PAH. - CONCLUSIONS: In this qualitative analysis, all 26 patients and 18 clinicians provided positive feedback on M/T FDC treatment, which was consistent across countries. Reducing the number of pills needed to treat PAH, through use of single-tablet M/T FDC, is highly valued by patients and endorsed by clinicians, who both felt the single-tablet combination therapy could have a positive effect on patients' well-being and increase treatment adherence.